Persistensi Bahan Bakar Fosil: Analisis Path Dependence dalam Bauran Konsumsi-Energi Indonesia Periode 1980–2015 - Harimbawa, Made (UI Scholars Hub, 2016)
Current fossil fuels use has created two major issues: environmental damage from greenhouse gas emissions and energy security. In the recent decades, development in science and technology along with increasing demand for shifting to cleaner and renewable energy sources have not yet changed the proportion of fossil fuel in Indonesia energy-consumption mix. One explanation to this phenomenon is the existence of path dependence that locks Indonesia’s technological systems and institutions into cycles of fossil fuels consumption, which in turn limiting the development of alternative technologies. Analysis using equilibrium dependent model suggests that this is the case: fossil fuels persistence in Indonesia is very high. The existence of path dependence is creating barriers, making it difficult for Indonesia to break out from its dependence to oil, coal, and natural gas.